(3OhQ GdeJZjQGJ GdJfXjejI hGdhXjajI ai JMSjf LhOI GdNOeI GdUMjI(B:s (3OQGSI ejOGfjI HGdeYgO Gdbhei ddChQGe (B- (3LGeYI GdbGgQI (B/s - (3KfGA eYhV Ydi CHhTMGJg s; (3LGeYI bfGI GdShjS s (3cdjI GdJLGQI HGdESeGYjdjIs (3bSe EOGQI GdCYeGds ([(3O(B.(3e(B]:s [(3O(B.(3f(B](3,s, 2014)
(3edNU HGddZI GdGfLdjRjI (B.s
(3GdeQGLY ef (B(194-203).s
(3OQLI OcJhQGg GdadSaI aj EOGQI GdCYeGd s
(3LGeYI bfGI GdShjS (B:(3cdjI GdJLGQI HGdESeGYjdjI (B:(3bSe EOGQI GdCYeGd (B.s
Keywords: (3LhOI GdNOeI GdUMjI s -- (3GdeYgO Gdbhei ddChQGe (B.s